Strategic studies: between rigour and subjectivity - Salgado Espinoza, Raúl (2018)
This paper proposes that the limited dialogue and debate amongst groups of academics from different regions and perspectives have contributed to the unlimited expansion of the strategic spectrum and the themes that cover strategic studies. From a methodological perspective and in order to develop this argument, this article provides a descriptive-analytical study of the literature of the field of strategic studies, from three different angles: worldwide, regional and national. The text develops with the fundamental premise that “strategy”, as object of study, has lost its original content as an analytical concept as a result of the broadening of its meaning.